Peran Media Massa dalam Konflik di Indonesia : Sebuah Alternatif Solusi? - Santosa, Bend Abidin (Departement of Islami Comuunication and Broadcasting, Faculty of Da'wah and Communication, State Islamic University of Sunan Ampel (UINSA) Surabaya Indonesia, 2016)
Indonesia is a country with diversified ethnics, religions and race. There are many ethnics, religion and race, unconsciously, in need of tolerance which otherwise can result in conflict and disunion. Mass media is one of instrument in mass communication process and it is the filter to select any news and sort of conflicting event to be presented.Objective of this study is to see how conflict-presenting mass media with peace journalism will be one of alternative solution in han dling conflicts in Indonesia. Research methodology being applied is descriptive qualitative method. While analysis being used is framing analysis.Results of this study state that mass media has significant roles in constructing public opinion due to the power to construct the reality in public in disseminating varied information and also values to community for the achievement of tolerance so that the conflict would not occurred